Antecedents and consequences of female consumer's attitude and lifestyle in facial care market - Kumar, Pranav (2015)
Evaluation of ethical marketing practices of businesses from a consumer perspective has often been prescribed as an international research direction, more particularly for the developing economies. In accordance with the above, this consumer study based in Malaysia investigated the antecedents and consequences of consumer attitude towards ethical marketing practices of firms depicted by product fairness, price fairness, and fairness aspects of marketing communications and channels of distribution in the facial care sector. Moderating influences of consumer lifestyle and demography were also taken into consideration in order to describe the scenario with enhanced precision and possibilities. The model under study was developed using the proven predictive power of the theory of planned behavior supported with the consumer decision process model. Relying on a survey research design, and following a rigorous multi stage sampling method, 483 female consumers falling within 15 years and above age range were surveyed from different parts of Malaysia. Descriptive analysis was done using SPSS, and inferential analysis using SmartPLS software, a variance based structural equations modeling tool. The findings revealed that product fairness, marketing communications, price fairness, and channels of distribution possess significant positive relationship with consumer attitude which further significantly predicts behavioral intention. Social factors and perceived behavioral control too were seen to predict behavioral intention which was further seen to influence the actual behavior of consumers. Consumer lifestyle as a whole, reflected through self-confidence, health consciousness, family orientation, religiosity, and women role and perception was found to have no moderation effect on the consumer attitude and behavioral intention relationship. The results of multi group analysis revealed that income of consumers exerts no moderation effect whereas education moderates the relationship of marketing communications, price fairness, and channels of distribution taken with consumer attitude. As Malaysian consumers exhibit serious concern towards ethical marketing practices of firms, it is recommended to the managers that they ensure fairness in their offerings, pricing, marketing communications and the way they make the products available to the consumers. Also, the policy makers are suggested to focus on creating awareness regarding the growing significance of ethical aspects, in addition to instituting desirable regulations